2020
DOI: 10.3389/fnsys.2020.00045
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ginkgolides in the Inflammatory Immune Response of Neurological Diseases: A Review of Current Literatures

Abstract: The inflammatory immune response (IIR) is a physiological or excessive systemic response, induced by inflammatory immune cells according to changes in the internal and external environments. An excessive IIR is the pathological basis for the generation and development of neurological diseases. Ginkgolides are one of the important medicinal ingredients in Ginkgo biloba. Many studies have verified that ginkgolides have anti-platelet-activating, anti-apoptotic, anti-oxidative, neurotrophic, and neuroimmunomodulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 99 publications
0
16
0
Order By: Relevance
“…Currently, LPS is used to constituents of Ginkgo biloba leaves and have characteristic powerful anti-inflammatory properties (10). Although several studies examining the anti-inflammatory effects of GA, GB and GC have been reported (11)(12)(13)(14)(15); to date, there has been little research exploring the relationship between GJ and RA inflammation, and the exact mechanism of the anti-inflammatory effect of GJ remains obscure. In the present study, using LPS-activated human synovial cells SW982, it was revealed that GJ pretreatment could attenuate LPS-induced production of pro-inflammatory mediators such as cytokines, PGE2 and NO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, LPS is used to constituents of Ginkgo biloba leaves and have characteristic powerful anti-inflammatory properties (10). Although several studies examining the anti-inflammatory effects of GA, GB and GC have been reported (11)(12)(13)(14)(15); to date, there has been little research exploring the relationship between GJ and RA inflammation, and the exact mechanism of the anti-inflammatory effect of GJ remains obscure. In the present study, using LPS-activated human synovial cells SW982, it was revealed that GJ pretreatment could attenuate LPS-induced production of pro-inflammatory mediators such as cytokines, PGE2 and NO.…”
Section: Discussionmentioning
confidence: 99%
“…GA has been revealed to suppress the expression of pro-inflammatory mediators [cyclooxygenase-2 (COX-2) and nitric oxide (NO)] and pro-inflammatory cytokines [tumor necrosis factor (TNF)-α, interleukin (IL)-6 and IL-1β] in LPS-treated mouse and human macrophages (11). Other CGs have exhibited anti-platelet-activating, anti-apoptotic, anti-oxidative, neurotrophic and neuroimmunomodulatory effects by inhibition of the mitogen-activated protein kinase (MAPK) and nuclear factor-κB (NF-κB) signaling pathways (12). Among these CGs, GB has the most obvious pharmacological properties, while little is known about GJ (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The cytokine targets cells via a specific G-protein-coupled metabotropic receptor (PAFR). The interaction between PAF and PAFR induces signal transmission in the humoral, autocrine, or paracrine way [8]. Activated PAFR triggers various intracellular signal cascades, including turnover of phosphatidylinositol, elevation in intracellular calcium concentration, and activation of kinases [9].…”
Section: Ginkgolides As Paf Inhibitors In Inflammation and Thrombotic Processmentioning
confidence: 99%
“…Ginkgolides are responsible for the inhibition of TLR4-mediated inflammatory response [8,14] . After binding to TLR agonists, such as bacterial or viral products, TLRs activate the adapter proteins (MYD88, TRAM, TIRAP), eventually activating the phosphorylation of NF-kB (nucleus factor kappa B) [15].…”
Section: Ginkgolides As Tlr4 Antagonistsmentioning
confidence: 99%
“…Many potential mechanisms in various tissues have been proposed to explain the protective actions of ginkgolides, including their effects on the platelet activating factor [ 131 , 132 , 133 ], generation of reactive oxygen species [ 134 , 135 ] and different signal transduction processes [ 135 , 136 , 137 , 138 , 139 ]—one of these actions has been recently connected to the role of the HO-1 system [ 138 , 140 ]. Thus, the effects and action mechanisms of Ginkgo biloba extract (EGb-761) were studied in ischemia/reperfusion-induced injury in rats [ 138 ], and it was found that levels of of creatine kinase-MB, lactate dehydrogenase, troponin T, TNF-α, IL-6 and IL-1β were significantly reduced in the drug-treated group in comparison with the drug-free control values.…”
Section: Ginkgo Biloba “Ginkgoflavonoids” and Ho-1mentioning
confidence: 99%